Plant Functional Genomics Methods and Protocols - Alonso, Jose M.; Stepanova, Anna N.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This second edition volume discusses the revolutionary development of faster and less expensive DNA sequencing technologies from the past 10 years and focuses on general technologies that can be utilized by a wide array of plant biologists to address specific questions in their favorite model systems. This book is organized into five parts. Part I examines the tools and methods required for identifying epigenetic and conformational changes at the whole-genome level. Part II presents approaches used to determine key aspects of a gene’s function, such as techniques used to identify and characterize gene regulatory networks. This is followed by a discussion of tools used to analyze the levels of mRNA, mRNA translation rates, and metabolites. Part III features a compilation of forward and reverse genetic approaches that include recent implementation of high-throughput sequencing in classical methodologies such as QTL mapping. The final two parts explore strategies to facilitate and accelerate the generation and testing of functional DNA elements, and basic computational tools used to facilitate the use of systems biology approached by a broad spectrum of plant researchers. Written in the highly successful Methods of Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Practical and timely, Plant Functional Genomics: Methods and Protocols, Second Edition highlights the latest developments in DNA sequencing technologies that are likely to continue shaping the future of functional genomics.
Epigenome Profiling of Specific Plant Cell Types Using a Streamlined INTACT Protocol and ChIP-seq -- Whole-Genome DNA Methylation Profiling with Nucleotide Resolution -- High-Throughput Nuclease-Mediated Probing of RNA Secondary Structure in Plant Transcriptomes -- Genome-Wide Mapping of DNase I Hypersensitive Sites in Plants -- Characterization of in-vivo DNA-Binding Events of Plant Transcription Factors by ChIP-seq: Experimental Protocol and Computational Analysis -- Identification of Direct Targets of Plant Transcription Factors Using the GR Fusion Technique -- Ribosome Profiling: A Tool for Quantitative Evaluation of Dynamics in mRNA Translation -- Tissue-Specific Gene Expression Profiling by Cell Sorting -- Translating Ribosome Affinity Purification (TRAP) Followed by RNA Sequencing Technology (TRAP-SEQ) for Quantitative Assessment of Plant Translatomes -- Rapid Immunopurification of Ribonucleoprotein Complexes of Plants -- Metabolomic Profiling of Plant Tissues -- Targeted Plant Genome Editing via the CRISPR/Cas9 Technology -- QTL Mapping Using High-Throughput Sequencing -- Quantitating Plant MicroRNA-Mediated Target Repression Using a Dual-Luciferase Transient Expression System -- Persistent Virus-Induced Gene Silencing in Asymptomatic Accessions of Arabidopsis -- A User’s Guide to the Arabidopsis T-DNA Insertion Mutant Collections -- Genome-Wide Association Mapping in Plants Exemplified for Root Growth in Arabidopsis thaliana -- Tilling By Sequencing -- SHOREmap v3.0: Fast and Accurate Identification of Causal Mutations from Forward Genetic Screens -- Software-Assisted Stacking of Gene Modules Using GoldenBraid 2.0 DNA-Assembly Framework -- Ligation Independent Cloning for Plant Research -- Gene Functional Analysis Using Protoplast Transient Assays -- Descriptive vs. Mechanistic Network Models in Plant Development in the Post-Genomic Era -- Analysis and Visualization of RNA-Seq Expression Data Using RStudio, Bioconductor, and Integrated Genome Browser -- Constructing Simple Biological Networks for Understanding Complex High-Throughput Data in Plants.
Keywords: Plant science; Botany; Plant Sciences